Vulnerabilidade ambiental da sub-bacia hidrográfica do rio Mandu, sul de Minas Gerais - Ribeiro, André Dos Santos (2014)
Water erosion is one the greatest cause of depletion of soils in Brazil and worldwide. Therefore, the aim of this work was to apply the Empirical Analysis of Environmental Fragility, to classify environmental vulnerability to erosion of the Mandu river watershed, southern Minas Gerais State. This, considering the environmental components: land use, relief, soils and climate, in descending order of priority established by Analytical Hierarchy Process (AHP), which interfered with the final outcome and is recommended when applying this method. In this way, it was established that most of the watershed land uses are inadequate. In this, 33,67% of the area should be permanent preservation and the usable sites, need to be properly managed, mainly pastures. So 52,91% would have low vulnerability. Also, the exposed soil elimination and the rearrangements in locals with temporary agriculture contribute much with attenuation of environmental impacts and phase out areas with very strong and strong vulnerability.